Bovine Delta Papillomavirus E5 Oncoprotein Interacts With TRIM25 and Hampers Antiviral Innate Immune Response Mediated by RIG-I-Like Receptors - De Falco, Francesca; Cutarelli, Anna; Gentile, Ivan; Cerino, Pellegrino; Uleri, Valeria; Catoi, Adriana Florinela; Roperto, Sante (Frontiers in Immunology, 2021)
Persistent infection and tumourigenesis by papillomaviruses (PVs) require viral manipulation of various of cellular processes, including those involved in innate immune responses. Herein, we showed that bovine PV (BPV) E5 oncoprotein interacts with a tripartite motif-containing 25 (TRIM25) but not with Riplet in spontaneous BPV infection of urothelial cells of cattle. Statistically significant reduced protein levels of TRIM25, retinoic acid-inducible gene I (RIG-I), and melanoma differentiation-associated gene 5 (MDA5) were detected by Western blot analysis. Real-time quantitative PCR revealed marked transcriptional downregulation of RIG-I and MDA5 in E5-expressing cells compared with healthy urothelial cells. Mitochondrial antiviral signalling (MAVS) protein expression did not vary significantly between diseased and healthy cells. Co-immunoprecipitation studies showed that MAVS interacted with a protein network composed of Sec13, which is a positive regulator of MAVS-mediated RLR antiviral signalling, phosphorylated TANK binding kinase 1 (TBK1), and phosphorylated interferon regulatory factor 3 (IRF3). Immunoblotting revealed significantly low expression levels of Sec13 in BPV-infected cells. Low levels of Sec13 resulted in a weaker host antiviral immune response, as it attenuates MAVS-mediated IRF3 activation. Furthermore, western blot analysis revealed significantly reduced expression levels of pTBK1, which plays an essential role in the activation and phosphorylation of IRF3, a prerequisite for the latter to enter the nucleus to activate type 1 IFN genes. Our results suggested that the innate immune signalling pathway mediated by RIG-I-like receptors (RLRs) was impaired in cells infected with BPVs. Therefore, an effective immune response is not elicited against these viruses, which facilitates persistent viral infection.